Pengaruh Investasi, Angkatan Kerja, Pengeluaran Pemerintah dan Tingkat Pendidikan Terhadap PDRB Jawa Timur - Alvaro Dimas Febrianto; Zainal Arifin (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
Gross Regional Domestic Product (GRDP) is a reference of GRDP in a region, where if a GRDP value in a region increases, it indicates an increase in the production process of items and services. Investment, labor force, government expenditure, and educational level are some of the indicators that can influence the changes of GRDP value in a region. The aim of this study is to analyze how the influence of Investment, Labor Force, Government Expenditure (Capital Expenditure, and High School Education Level. This study was a quantitative study using multiple linear regression analysis with time series, which was analyzed with SPSS 26 software. The results of this study show that simultaneously, variables of Investment, Labor Force, Government Expenditure (Capital Expenditure), and High School Education Level significantly influence the GRDP in East Java Province in 1990-2020. The coefficient of determination (R2) shows that 80.3 percent of variables influence employment, and the remaining 19.7% is explained by other variables not examined in this study. Partially, Investment, Labor Force, Government Expenditure (Capital Expenditure), and High School Education Level significantly influence the GRDP in East Java Province. Keywords: Investment, Labor Force, Government Expenditure (Capital Expenditure), High School Education Level